Sustentabilidade de sistemas de produção da pecuaria familiar: uma análise a partir da expansão da soja sobre áreas de bioma Pampa - Nicoloso, Carolina da Silveira (2017)
In the Pampa biome, the increase of cultivated areas of soybeans occurs over areas previously destined for animal production, being introduced in systems of production of the family livestock, driven by the profitability of the crop. In view of this phenomenon the objective of this thesis is to evaluate the sustainability of family livestock production systems inserted in the Pampa biome, in the central region of Rio Grande do Sul, using the MESMIS methodology. In the first article, three systems of production of the family livestock that occur in the Pampa biome, CN (Natural Grassland), CN+C (Natural Grassland + other cultives) and CN + S (Natural Grassland + Soybean) were compared. A significant difference (p <0.10) was found for the "Productivity" attribute between the CN + C and CN + S systems, the first being higher than the second. For the other attributes of sustainability, there were no significant differences between the systems of production of family farms studied. In the second article the evolution of the sustainability of the CN, CN + C and CN + S systems over time was analyzed. The MESMIS method was applied to the same production systems and rural properties in 2014 and 2016, after approximately 24 months between observations. The results of the two periods were compared to each other. A significant difference (p <0.10) was found for the "Productivity" attribute between the CN + C and CN + S systems, the first being higher than the second, in 2014 and 2016. In the evaluation carried out in 2016, a difference (P <0.10) for the attribute Stability, being the CN system superior to the others, which did not differ between them. When comparing the results from within each system, between the two periods of 2014 and 2016, the CN + C system presented significant growth (p <0.10) after the interval between observations. In the third article, the typology of 90 family livestock production systems in Pampa biome was performed according to sustainability, using the MESMIS method and cluster analysis. The production systems were grouped into three different groups (1, 2 and 3). Group 1 was the least sustainable, with a higher percentage of crops in the systems, more soybean crops, lower share of income from livestock production, less native field area. Group 2 presented greater sustainability, with smaller areas of crops in relation to the total area, more native field in the systems, more standardized herd, greater crop diversification and a higher level of formal education and producers' participation. Group 3 presented higher productivity, self-sufficiency equal to the other groups, and for the other attributes it was equal to group 1 and smaller than Group 2 (p <0.05). The results obtained in the first two articles, where few differences were observed among the production systems studied, are confirmed by the results obtained in the third article with the typology of the production systems. For the study object proposed here, the results show that the greater or lesser sustainability lies in the balance between activities, between livestock and agriculture.